Propofol Protects Myocardium From Ischemia/Reperfusion Injury by Inhibiting Ferroptosis Through the AKT/p53 Signaling Pathway - Li, Shengqiang; Lei, Zhen; Yang, Xiaomei; Zhao, Meng; Hou, Yonghao; Wang, Di; Tang, Shuhai; Li, Jingxin; Yu, Jingui (Frontiers in Pharmacology, 2022)
The protective mechanism of propofol on myocardial ischemia/reperfusion (I/R) injury remains poorly understood. Previous studies have shown that ferroptosis plays an important role in myocardial I/R injury. Our study hypothesized that propofol protected myocardial I/R injury from inhibiting ferroptosis through mediating AKT/p53 signaling pathway. Two tools were used in this study: ferroptosis-inducing agent erastin (E) and AKT inhibitor MK2206 (MK). H9C2 cells were treated with no reagents (C), erastin for 24 h (E), and propofol (P) for 1 h before erastin (E+P). N=3. The cell viability, reactive oxygen species (ROS), and the expression of antioxidant enzymes (ferritin heavy chain 1 (FTH1), superoxide dismutase-2 (SOD-2), and glutathione peroxidase 4 (GPX4)) on H9C2 cells were assessed. Rat hearts were treated with KrebsHenseleit solution (KH) for 120 min (C), with (I/R+P) or without (I/R) propofol for 20 min before stopping perfusion for 30 min and reperfusion for 60 min, with (I/R+P+MK) or without propofol (I/R+MK) after MK2206 for 10 min before stopping perfusion. N=6. The histopathology, mitochondrial structure, iron, and the expression of antioxidant enzymes on myocardium were assessed. Erastin increased H9C2 cell mortality and reduced the expression of antioxidant enzymes. I/R, which abated the expression of antioxidant enzymes and increased iron or p53 (P<0.05), boosted myocardium pathological and mitochondrion damage. Notwithstanding, propofol restrained all these influences, which were antagonized by MK (P<0.05). AKT siRNA inhibited propofol-induced antioxidant enzyme expression (P<0.05). The study confirms that propofol protects myocardium from I/R injury by influencing AKT/p53 signal pathway-mediated ferroptosis mechanism.